PhotoAlbum : organizing photographs, understanding aesthetic - Oh, Daniel Yu Hong (2011)
With the evolution of technologies, the cost of digital camera devices has been efficiently reduced. Users tend to have a large collection of digital photographs in their personal computer due to the high availability and low cost of cameras. Thus, there is an increase demand of having applications that allow users to organise and edit their photographs.